Geological observations in Gjelsvikfjella and Mühling-Hofmannfjella - Bucher-Nurminen, Kurt; Ohta, Yoshihide; Austrheim, Håkon; Dallmann, Winfried K (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geologi

Geology around the Norwegian Antarctic station "Troll", Jutulsessen, Dronning Maud Land - Dallmann, Winfried K; Austrheim, Håkon; Bucher-Nurminen, Kurt; Ohta, Yoshihide (Norsk Polarinstitutt, 1990)
During the Norwegian Antarctic Research Expedition 1989/90, a pennanent, unmanned research station was raised in Jutulsessen, Gjelsvikfjella, western Dronning Maud Land. The present report is a description of the geology of the area accessable from the station. Exposures of rocks in this part of Dronning Maud Land are restricted to a coastal mountain chain at c. 200-250 km distance from the ice shelf edge at elevations between 1000 and 3000 m. Quaternary deposits are particularly restricted to the inner parts of the Jutulsessen glaeier cirques. Deposits are till and talus which locally are admixing at slope angles of c. 25°. Moraines are poorly developed. Patterned ground ('stone pits') are common at slope angles below c. 15°. Recently active phenomena of special interest are ice-margin meltwater lakes with pingo-like 'blisters " the deep frost-shattering all over the mountain walls and hoIes in rock surfaces as a result of wind activity with grinding particles. The bedrock belongs to the East Antarctic craton. The area under consideration (western Miihlig-Hofmannfjella and Gjelsvikfjella) consists of high-grade metamorphic rocks and fonns one of the world's best exposed granulite terranes. Orthogneisses and minor metasediments have been intruded by a series of charnockites, partly altered to granulites (the 'Svarthamaren charnockite complex'), and a sequence of dyke rocks. Migmatization has affected large parts of the gneisses. Both gneisses and granulites/charnockites show abundant evidence of transition from granulite to amphibolite facies and vice versa, and the important role of fluid-rock interactions leading to these processes can be studied. The gneisses at Jutulsessen show a complex defonnation history. They are thought to be derived from granitic intrusions, though minor amounts of high-grade metamorphic, metapelitic gneisses may represent their original host rocks. Early tectonism (c. 1000-1200 m.y.) produced gneissosity, compositional banding and a leucosome phase under high-grade metamorphic conditions. This was followed by multiple and complex intrusive activity, partial migmatization and a tectonic overprint with abundant shear defonnation under amphibolite-facies conditions (c. 450-500 m.y.).
Keywords: Dronning Maud Land; NARE 1989/90; berggrunnsgeologi; geologi

Geodetic measurements in Dronning Maud Land - Eiken, Trond; Luktvasslimo, Brit Åse; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geodesi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Medical contingency and biomedical research - Molvær, Otto Inge; Bendiksen, Fredrik S; Reitehaug, Per-Ivar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; biomedisin; medisin

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella, Dronning Maud Land, east Antarctica - Ohta, Yoshihide; Tørudbakken, Bjørn; Shiraishi, Kazuyuki (Polar Research, 1990)
As a part of the Norwegian Antarctic Research Expedition 1984/85, geological mapping was performed in Gjelsvikfjella and western Muhlig-Hofmannfjella, Dronning Maud Land. The northern part of Gjelsvikfjella is dominated by the Jutulsessen metasupracrustals which have been intruded by a major gabbroic body and several generations of dykes. To the south the metasupracrustals gradually transform into the Risemedet migmatites. In western Muhlig-Hofmannfjella the bedrock is dominated by the large Svarthamaren Charnockite batholith. The batholith is bordered by the Snotoa metamorphic complex outcropping to the south and west in Muhlig-Hofmannfjella and it is characterized by a high content of partly assimilated country rock inclusions. Mineral paragenesis and geothermometry/geobarometry suggest a two-stage tectonothermal-igneous history with an initial intermediate pressure, upper amphibolite to granulite facies metamorphism followed by high temperature transformations related to the charnockite intrusion. The age of the initial tectonothermal event is probably about 1,100 Ma. Geochronological work in the present study (Rb/Sr whole rock) gave an age of 500 +/- 24 Ma for the Svarthamaren Charnockite, interpreted to record the age of crystallization. Late brittle faulting and undeformed dolerite dykes outcropping in Jutulsessen are believed to be related to Mesozoic crustal stretching in the Jutulstraumen-Pencksokket Rift Zone to the west.
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi